Variasi Temperatur Termophilic Pada Digester Biogas Berbahan Baku Limbah Kulit Durian - Prakasa, I Made Panji Tirta; Sutasoma, I Wayan Gde; Tapa, I Gede Fery Surya; Dayanti, Made Ari Riska (Politeknik Negeri Jakarta, 2025)
The global energy crisis and Indonesia's dependence on fossil fuels (BBF) have driven the need to explore renewable energy sources. Biogas, as a sustainable solution, is produced through anaerobic degradation of materials with methane (CH₄) 50–75% and carbon dioxide (CO₂) 30–45% as its dominant components. Agro industrial waste such as durian peel shows great potential for biogas production, as Indonesia produces more than 19 thousand tons of durian annually according to the 2024 Statistics Indonesia report. Utilizing durian peel is ideal since its composition (65–80%) is significantly higher than that of the pulp (20–35%) and seeds (5–15%). This study employed a substrate ratio of 5 grams of total solids (TS) + 100 mL of inoculum + 200 mL of distilled water, with intermittent stirring (three times per day, 1 minute per session). The tested temperature variations under thermophilic conditions 40°C, 45°C, and 50°C, including one control without heating. The analysis focused on daily pressure accumulation and gas composition profiles (CH₄ and CO₂). The results show that 40°C (thermophilic condition) achieved maximum efficiency due to optimal methanogenic microbial activity, producing higher methane (CH₄) yield compared to other temperatures. This study contributes to the development of renewable energy from agricultural waste in tropical regions and supports Indonesia’s national energy transition program.